Les mécanismes d'incitations fiscales à l'investissement des entreprises étrangères en France et au Gabon - Engone, Kénaelle Cyndie (Université de Limoges, 2019)
L’attractivité territoriale des Etats se trouve au centre des préoccupations tant au niveau national qu’international. Les mesures fiscales dérogatoires destinées à attirer des investissements étrangers s’avèrent nombreuses et complexes, en raison non seulement de l’influence internationale, mais également des hésitations et de l’accumulation des règles nationales. Au Gabon et en France, les incitations fiscales d’attraction territoriale ont été instruites dans des domaines d’activités clés de l’économie. Elles participent ainsi à l’industrialisation de ces pays. Cependant, au-delà de l’industrialisation, ces mesures dérogatoires visent à développer certaines zones du territoire, et surtout à lutter contre le chômage. Néanmoins, loin de toujours parvenir aux résultats escomptés, ces mesures finissent parfois, au fil des années et des modifications successives à se complexifier, les rendant illisibles. The territorial attractiveness of states is at the center of national and international. Derogatory tax measures designed to attract foreign investments are numerous and complex, not only because international influence, but also hesitations and the accumulation of national rules. In Gabon and France, territorial attraction tax incentives have been educated in key activity areas of the economy. They thus participate industrialization of these countries.However, beyond industrialization, these derogations aim to develop certain areas of the territory, and especially to combat unemployment. Nevertheless, far from always achieving the expected results, these measures end up sometimes, over the years and successive modifications to become more complex, making them unreadable.
Keywords: Aides d’Etat; Attractivité (géographie); Competitiveness; Compétitivité; Emploi; Employment; Fiscalité; Gabon; Impôt; Incitations fiscales; Industrialisation; Investissements; Investments; State aids; Tax incentives; Taxe

L'introduction des entreprises à la Bourse régionale des Valeurs Mobilières (BRVM) dans la zone UEMOA : cas de la Société Ivoirienne de Banque (SIB) - Fegbo, Ahonon Emmanuella Ines; Fassoukoye, Safi (Université Mouloud Mammeri, 2019)
Cette étude a pour objectif de connaitre les différentes étapes de l’introduction à la Bourse régionale des valeurs mobilières (BRVM) en tant que place financière régionale de l’UEMOA, régulé par le conseil régional de l’Epargne Publique et des marchés financiers. Pour atteindre cet objectif, nous avons émaillés l’organisation du marché financier dans une approche visant à définir les différents intervenants et leur rôle. Ensuite, nous avons analysés l’activité boursière du marché. Les indicateurs de performance principalement relevés sont le rendement, la liquidité, le volume de transactions et le risque du marché. Le potentiel de la BRVM est encore à exploiter au regard de l’activité économique de la sous-région. Toutefois, le dynamisme du marché boursier est intéressant surtout du fait qu’il offre un rendement intéressant auprès des intéressés. Nous avons soumis les différents indicateurs du marché à une analyse comparative de son évolution à l’échelle des Bourses africaines, afin d’évaluer son degré d’attractivité. Nous recommandons des ajustements sur les différents points relevés visant l’essor de la place financière de la BRVM tout en démontrons les résultats de notre recherche.
Keywords: BRVM; Banque; Bourse; Bourse régionale; Indices boursiers; Marché financier

Le crédit réel individuel : problèmes juridiques et éthiques - Poaty, Marie-Laure (Université de Bordeaux, 2019)
Ce travail se propose d'étudier les aspects juridiques du crédit dit réel dans une confrontation implicite au crédit bancaire qui semble aujourd'hui l'emporter dans le domaine des échanges, en utilisant un système de garantie tiré des suretés réelles. La comparaison engagée est destinée à montrer quel rôle occupe en particulier la réserve de propriété et la fiducie dans le domaine classique de la vente civile et commerciale à destination des particuliers. Au-delà d'une approche technique, il s'agit de restituer un sens aux définitions des droits personnels et réels dans le langage des sources du droit. Il s'agit aussi de s'attacher aux valeurs de justice en terme éthique qui fondent le support de ces droits : dignité des personnes et droit des biens qui tiennent au mécanisme synallagmatique engagé (équivalence des prestations). Mais, il sera aussi tenu compte du rôle parfois déstabilisateur d'éléments économiques extérieurs dans la mesure où ils déséquilibrent les mécanismes juridiques classiques en mettant en concurrence crédit bancaire et crédit réel, alors même qu’il semble que le dernier soit d’avantage justifié. This work proposes to study the legal aspects of trade credit in the case of an implicit impasse with bank credit that seems to prevail today in the field of trade, by using a guarantee system derived from real collateral. The comparison undertaken is intended to show the role played in particular by the retention of title and the trust in the classic field of retail sale to individuals. Beyond a technical approach, it’s about restoring a meaning to definitions of personal and real rights in the language of the law or regulations. It is also a question of attaching to the values of justice in ethical terms which are at the foundation of these rights: the dignity of people and the right to possess goods which are linked to the equality of benefits. But it will also be taken into consideration the sometimes-destabilizing exterior economic elements, in the measure that they destabilize the classic legal mechanisms by putting bank credit and trade credit in competition, even though it seems that the latter is more justified.
Keywords: Bank credit; Collateral; Crédit (droit); Crédit bancaire; Crédit réel; Ethic; Property; Propriété; Sûretés; Sûretés (droit); Trade credit; Éthique

Les prix de transfert et le principe de pleine concurrence dans les pays en développement - Randriamanalina, Tovony (Université Paris-Dauphine, 2019)
La fixation du prix de pleine concurrence par les administrations fiscales des pays en développement soulève des questions singulières. L’objectif fondamental recherché à travers la fixation des prix de transfert est l’affectation de la juste assiette de l’impôt à chaque État concerné par les transactions intragroupes, c’est-à-dire au sein des groupes multinationaux de sociétés. L’OCDE et ses pays membres estiment que le meilleur moyen pour parvenir à cet objectif est de vérifier que le prix de transfert en cause respecte le principe de pleine concurrence, lequel repose sur une comparaison entre les prix pratiqués par les sociétés appartenant à un même groupe et ceux pratiqués pour des opérations similaires, par des entreprises indépendantes. Toutefois, cet objectif n’est pas toujours atteint dans la pratique. Favorisé par l'OCDE, le principe de pleine concurrence suppose la mise en œuvre d’une analyse des faits et circonstances des transactions de chaque contribuable. L’OCDE recommande cinq méthodes pour cette analyse, jugée très subjective, donnant aux multinationales une grande liberté pour se structurer afin de minimiser les coûts fiscaux qu'elles encourent. A l’issu du projet BEPS de l'OCDE/G20, le principe de pleine concurrence continue d’être le standard international pour l'évaluation des prix de transfert. Toutefois, ce principe n’est pas suffisamment pragmatique pour les administrations fiscales que l’on peut considérer comme faibles, car il comporte de nombreuses échappatoires qui peuvent compromettre la détermination de l'assiette fiscale. Pour une imposition effective des groupes multinationaux de sociétés, notre thèse suggère deux arguments principaux. D’abord, elle propose des mesures à court terme qui reposent sur la simplification des règles actuelles afin de permettre aux administrations fiscales de collecter des recettes fiscales avec les moyens dont elles disposent. Néanmoins, ces mesures sont provisoires et transitoires étant donné qu’elles reposent sur des méthodes unilatérales jugées défaillantes. Ensuite, notre thèse soutient l’idée que la taxation unitaire avec la répartition formulaire est, à long terme, la meilleure solution, car elle est plus équitable pour toutes les parties. Our thesis addresses taxation of transfer pricing and the arm’s length principle (ALP) in developing countries. Transfer pricing rules aim to accurately reflect the economic contribution of a multinational company (MNC) in each of the various jurisdictions in which it operates. The objective of the TP rules is to ensure that the various entities of an MNC report the real corresponding taxable profits in their jurisdiction.However, this objective is not always attained in practice. Favored by the OECD, the ALP approach requires an individual analysis of the facts and the situation of each taxpayer. There are five approved methods for this analysis, therefore it is eventually highly subjective, giving MNCs much freedom to structure themselves to minimize the tax costs they incur. Following the OECD/G20 BEPS Project, ALP has continued to be the international standard for assessing TP. However, the ALP is not a practical approach for developing countries, as it has many loopholes that can jeopardize the tax base. This thesis has two main arguments. First, it proposes some short-term strategies to make the ALP framework workable for developing countries’ tax administrations, although they are only a stopgate solution since they are still based on a flawed approach. Second, this chapter supports the judgment that unitary taxation with Formulary Apportionment (FA) is the best long-term solution that is fair to all parties.
Keywords: Administration fiscale; Arm’s length principle; Developing country; Droit fiscal (droit international); Droit fiscal international; Impôt (administration); Impôt (procédure); International tax law; Pays en développement; Principe de pleine concurrence; Prix de cession interne; Prix de transfert; Soft law; Tax administration; Taxation unitaire; Transfer pricing; Unitary taxation

Vers une maîtrise du risque bancaire systémique - Maurin, Alexandra (Université Paris-Dauphine, 2019)
L'essor de la RSE, tant au sein des sociétés qu'au travers des concertations internationales, illustre l'importance qu'ont pris l'éthique et la morale dans les relations d'affaires. Le banquier y tient une place centrale puisqu'il est « le moteur de toutes les activités de son temps ». Du fait de son rôle prépondérant, aussi bien pour l'économie réelle que sur les marchés financiers, il devrait agir en précurseur du développement de la RSE. Pourtant, lors de la crise de 2007, l'incitation déraisonnée au surendettement des particuliers et le recours à la titrisation pour faciliter la diffusion d'actifs toxiques ont démontré une amoralité générale des banques dans la conduite de leurs affaires. De cette crise de grande ampleur ressortent des questionnements sur l’impact de l’aléa moral sur la stabilité des États et la volonté d’apporter des réponses juridiques au risque bancaire systémique, afin de responsabiliser les banquiers et d’éviter que l’Histoire ne se répète.
Keywords: Aléa moral; Banks' liability; Banque universelle; CSR; Corporate Social Responsibility; Crise économique; Droit des affaires; Economic crisis; Moral hazard; RSE; Responsabilité du banquier; Responsabilité sociétale; Responsabilité sociétale des entreprises (RSE); Risque financier; Risque systémique; Systemic risk; Universal banks

The Impact of Economic Institutions on Small Firms in Developing Countries - Pouliquen, Victor (Ecole des Hautes Etudes en Sciences Sociales, 2019)
In many developing countries, economic institutions are failing. This translates into structural problems such as widespread informality, rampant corruption and the impossibility for governments to raise taxes. This thesis study how economic policies affect economic institutions in developing countries. It focuses on two broad questions: (1) What are the effects of policies to reduce informality? and (2) how are new technologies reshaping the way governments collect taxes?The first chapter uses a randomized experiment to study the introduction of a new legal status in Benin, created to make it easier for small firms to become formal. To make this new status attractive, the government added supplementary incentives designed to enhance the presumed benefits of formalizing. We find that few firms register when just given information about the new regime, but our full package of supplementary efforts boosts formalization by 16.3 percentage points. However, this formalization does not bring firms higher sales, profits or access to credit, and the cost of formalizing these firms exceeds the added taxation they will pay over the next decade. We show how better targeting of these policies towards firms that look more like formal firms to begin with can increase the formalization rate and improve cost-effectiveness. The second chapter studies the impact of formalization on intra-household relationships, still in Benin. The idea behind this chapter is that formalization changes effective property rights by clarifying who in the household is the legal owner of the business and who will keep it in case of divorce. The causal effect of formalization is identified using the same random experiment used for the first chapter. We find first that formalization increases entrepreneurs' (both male and female) control over household revenue. They contribute proportionally less to household expenditures and to the personal expenses of their partner. Second, using a behavioral game, we find strong gender differential effects of formalization on the probability that entrepreneurs pay to hide a windfall transfer from their spouse. Female entrepreneurs are much more likely to pay to hide, while male entrepreneurs are much less likely to do so. Using a theoretical model, we show that this result is compatible with the idea that women entrepreneurs are constrained and cannot invest as much as they would like in their own business. Women who became formal hide the windfall transfer more because they have more property rights and want to invest more in their business. Our conclusion is that formalization has important effects on intra-household dynamics.The third and final chapter of this thesis deals with the second question and examines how internet is changing the way taxes are collected. Specifically, we study the impact of electronic tax filing (e-filing) for small firms to replace in-person submission of paper-based forms to tax officials. We examine the impact of e-filing on compliance costs, tax payments, and bribes payments using experimental variation and data from Tajikistan firms. We find that firms that e-file have lower compliance costs, spending five fewer hours each month on fulfilling tax obligations. There are no significant average effects of e-filing on tax or bribe payments, but significant heterogeneity exists across firms by their baseline likelihood of tax evasion. Among firms previously more likely to evade, e-filing doubles tax payments, likely by disrupting collusion with officials. Conversely, among firms less likely to have been evading, e-filing reduces tax payments, suggesting that officials had previously required them to pay more. These firms also pay fewer bribes, as e-filing reduces opportunity for extortion. Our conclusion is that e-filing reduces compliance costs and makes the distribution of tax payments across firms arguably more equitable. Dans les pays en développement, les institutions économiques sont souvent défaillantes. Cela se traduit par des problèmes structurels tels que l’omniprésence du secteur informel, la corruption généralisée et l’incapacité des États à collecter les impôts. Cette thèse porte sur les politiques publiques permettant d’améliorer le fonctionnement des institutions économiques. Elle se focalise sur deux questions : (1) Quels sont les effets des politiques de réduction de l’informalité ? et (2) Comment les nouvelles technologies affectent la collecte des taxes ? Le premier chapitre étudie à l’aide d’une expérimentation aléatoire l’introduction d’un statut légal facilitant la formalisation des petites entreprises au Bénin. Afin de rendre ce statut attractif le gouvernement l’a accompagné d’incitations supplémentaires créés pour amplifier les bénéfices potentiels de la formalisation. Nous trouvons que très peu d’entreprises se formalisent lorsqu’elles reçoivent uniquement de l’information sur le nouveau statut. Cependant, lorsque l’information est combinée aux incitations, la formalisation augmente de 16,3 points de pourcentage. En revanche, les effets sur les performances des entreprises sont limités, et le coût des incitations est supérieur au total des impôts qu’elles paieront pendant les 10 prochaines années. Enfin, nous montrons comment un ciblage sur les entreprises ayant des caractéristiques proches des entreprises déjà formelles améliorerait l’efficacité de ce type de programme. Le second chapitre étudie l’impact de la formalisation sur les relations intra-ménages, toujours au Bénin. Dans ce contexte, la formalisation renforce les droits de propriété et clarifie au sein des ménages qui est le propriétaire légal de l’entreprise, et qui la gardera en cas de divorce. L’effet causal de la formalisation est identifié à l’aide de l’expérimentation aléatoire déjà utilisée pour le premier chapitre. Nous trouvons que les entrepreneurs s’étant formalisés ont plus de contrôle les ressources de leur ménage. Ils ou elles contribuent proportionnellement moins aux dépenses du ménage et transfèrent moins d’argent à leur partenaire. Deuxièmement, en utilisant un jeu comportemental dans lequel les entrepreneurs peuvent cacher un transfert monétaire à leur partenaire, nous trouvons que les femmes qui se sont formalisées cachent davantage à leur mari. A l’aide d’un modèle théorique, nous montrons que ce résultat est compatible avec l’idée que les femmes ne sont pas libres d’investir comme elles le souhaiteraient dans leur entreprise et doivent le faire secrètement. Notre conclusion est que la formalisation a des effets importants sur les dynamiques intra-ménage. Le troisième chapitre utilise une expérimentation aléatoire conduite au Tadjikistan pour étudier l’impact d’un système permettant aux entreprises de déclarer leurs taxes en ligne plutôt que de soumettre un formulaire en personne. Nous trouvons que ce système réduit le temps passé par les entreprises pour remplir leurs obligations fiscales de 5 heures par mois. Nous ne trouvons pas d’effets sur le montant des impôts payés ni sur le versement de pots-de-vin. En revanche, l’absence d’effets moyens masque une importante hétérogénéité. Les entreprises le plus susceptibles de faire de l’évasion fiscale dans le système précédent payent davantage d’impôts quand elles déclarent en ligne, probablement car elles ne peuvent plus entrer en collusion avec les agents des impôts. À l'inverse, les entreprises qui étaient les moins susceptibles de faire de l’évasion, payent moins des taxes quand elles déclarent en ligne, suggérant qu’elles étaient forcées de payer plus d’impôts avant. Ces entreprises paient également moins de pots-de-vin, ce qui suggère que déclarer en ligne offre une protection contre le risque d'extorsion de la part des agents du fisc. Notre conclusion est que permettre la déclaration des taxes en ligne a rendu l’appareil fiscal à la fois plus efficace et plus juste.
Keywords: Droits de Propriétés; Electronic Tax Filing; Impôt; Impôt (recouvrement); Informality; Informalité; Innovation; Intra-Household Relationships; New Technologies; Nouvelles Technologies; Paiement en ligne des Taxes; Petites Entreprises; Petites et moyennes entreprises; Property Rights; Propriété; Relations Intra-Ménage; Small Firms; Taxation; Économie souterraine

Essai d'une théorie juridique de la monnaie à partir de la notion de cours - Zanolli, Romain (Université Paris Cité, 2019)
Les mutations monétaires du XXIe siècle alimentent un renouvellement de la pensée monétaire. Qu'il s'agisse de la monnaie unique européenne, de l'invention de la monnaie électronique, de l'adoption d'un droit européen des monnaies (services de paiement, réserves intégrales), le législateur a façonné de nouvelles règles monétaires. Pour rationaliser ces règles disparates, cette thèse propose une théorie juridique de la monnaie construite à partir de la définition de la notion de « cours ». Pour isoler puis définir l'objet du cours, les sciences juridiques présentent l'avantage de dissocier le fait du droit. Cette logique permet de faire le départ entre le phénomène monétaire qui relève du fait (« fait social total » selon Durkheim) et sa manifestation dans la société au moyen des règles formalisées. Un classement doctrinal permet de distinguer, depuis la fin du XXe siècle, deux catégories de règles : celles de la « monnaie abstraite » qui président à la définition de l'unité de compte, et celles des « monnaies concrètes » qui organisent l'émission et la circulation monétaire. Seules ces dernières peuvent être l'objet d'un cours. Or une définition restrictive du cours (le cours légal) n'admet comme monnaies concrètes que les monnaies matérielles (billets et pièces). L'admission des monnaies immatérielles parmi les monnaies concrètes oblige à rompre avec la doctrine classique qui les assimile à des créances. Les monnaies immatérielles sont des objets du droit monétaire dont la remise (des fonds) éteint les promesses (les créances). Face à l'impérative nécessité de distinguer dettes et monnaies, on propose de créer une nouvelle catégorie nommée « monnaie civile ». Cette catégorie accueille les règles gouvernant les pratiques monétaires (les dettes et les créances) qui ne relèvent pas du fonctionnement du système monétaire (monnaies abstraite et concrètes). Le fonctionnement des monnaies concrètes, notamment entre le détenteur de monnaies et le banquier, prend la forme d'un triptyque : les fonds (1) sont stockés sur des supports monétaires (2. Billets, comptes...) et transférés d'un support à l'autre au moyen d'instruments de paiement (3. Chèques, cartes...). La différenciation entre les monnaies concrètes matérielles (espèces) et immatérielles (comptes) repose sur le lien entre les fonds et leur support monétaire : indissociable pour les premières, articulé pour les secondes. Ont cours de monnaies, les seules monnaies concrètes, à l'exclusion des monnaies abstraite et civile. Le dispositif cours légal (dès le Code pénal de 1810) traite distinctement la définition et la circulation des monnaies concrètes matérielles, ce qui dans les sciences juridiques traduit la notion et le régime. On nomme ces deux versants du cours légal respectivement « cours d'émission » et « cours de circulation ». Le premier désigne les règles juridiques qui font qu'une chose devient monnaie (du papier au billet). Quant au second, suivant la dualité du terme de cours, il définit les modalités de circulation. Il se subdivise en un « cours d'acceptation », qui définit les conditions de réception et un « cours de valeur », qui définit la valeur de réception. Ces règles du cours ont été au fondement de la définition juridique des monnaies. Cette thèse a recours au même fondement pour donner cours aux monnaies immatérielles (scripturales et électroniques). Le prisme du cours permet alors d'unifier les règles éparses qui régissent le cours d'acceptation et de valeur des monnaies immatérielles. Il en résulte une théorie renouvelée de la monnaie qui n'est plus centrée sur une compréhension restrictive du dispositif juridique du cours légal. Après avoir été « démétallisées », les monnaies dématérialisées s'offrent au XXIe siècle dotées d'un fondement juridique. Libéré du poids du cours légal des billets, le cours des monnaies immatérielles ouvre la voie à la définition des monnaies communes d'une société sans espèces.
Keywords: Banking law; Banque; Banques; Comptes; Cours légal; Currencies; Currency; Droit; Droit monétaire; Instruments de paiement; Legal tender; Monetary system; Monetary value; Money; Monnaie; Monnaie électronique; Monnaies virtuelles; Système monétaire; Systèmes de paiement; Valeur monétaire; Virtual currencies

Personal Property Security Law: International Ambitions and Local Realities - Castellano, Giuliano; Tosato, Andrea (International Business Law, 2019)
Personal property security law is a key element of “access to credit” and “financial inclusion”. The prevailing view is that a legal framework enabling the effective use of personal property as collateral markedly benefits both lenders and borrowers. Lenders can offer financing at a lower cost thanks to reduced credit risk; borrowers can access funding by leveraging the otherwise unavailable value of the assets integral to their operations. Over the past century, the priorities of personal property security law have evolved fundamentally. As small and medium-sized enterprises (SMEs) and individual entrepreneurs have become the growth engine of both developed and developing economies, legislators have grown sensitive to the financing needs of these entities. In parallel, the advent of the information society has demanded that lawmakers address squarely the rules governing the use as collateral of intangibles such as “receivables”, “intermediated securities”, “non-intermediated securities”, and “intellectual property rights”, rather than confine their gaze to tangibles such as industrial machinery, mobile equipment and inventory. Concurrently, the increasingly transnational nature of both economic development policies and commercial activity have engendered the need for global principles and standards for asset-based lending. To address these novel priorities and promote a healthy and vibrant credit ecosystem, international and regional organizations have undertaken projects aimed at modernizing and harmonizing personal property security law. Over time, these efforts have yielded a panoply of legal instruments. Binding conventions have been adopted to unify the rules of discrete facets of personal property security law, while soft-law texts, such as model laws and legislative guides, have been formulated to supply comprehensive legal templates to lawmakers keen to revise their domestic legal regimes. Nevertheless, states have struggled to assimilate these international efforts into their domestic legal systems. Common law jurisdictions have been loath to abandon the familiarity and safety of the path paved by centuries of case law; in similar vein, civil law jurisdictions have resisted inducements to renovate the normative infrastructure erected by the codifications of the 19th century. This Chapter explores the tension between international ambitions and local realities, with a special focus on the issues encountered in civil law jurisdictions. To this end, the case of Italy is examined as a living experiment in comparative personal property security law. In this jurisdiction, the recent enactment of a non-possessory security device, absent a comprehensive reform of the country’s civil code affords important lessons for any civil law system which might be pondering personal property security law reforms. More profoundly, it epitomizes the gap that separates the aspirations of international legal instruments from their effective implementation in domestic contexts. This analysis is divided into two parts. The first reviews international and regional legal initiatives that have shaped the personal property law landscape and then identifies a set of core tenets shared among them. In the second part, attention shifts to Italy, scrutinizing both the personal property security legal edifice originally constructed in this jurisdiction and the attempts to overhaul it that have taken place over the past three decades. This is followed by a critical appraisal of the current state of the law, by reference to the aforementioned core tenets of personal property law reform.
Keywords: Commercial Law; Law Reform; Non-possessory Pledge; Personal Property Security Law; Secured transactions

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Harmonisation des normes comptables internationales et OHADA : une analyse critique des parties prenantes - Yepdo, Florentin Gaël; Nyasseu, Emma Joachim; Tatang Atabonfack, Pulchérie Léonie (Revue du Contrôle de la Comptabilité et de l’Audit, 2019)
Face à la mondialisation des économies et la globalisation des marchés, le désire d’avoir un langage commun s’est de plus en plus fait ressenti. Pour assoupir ce besoin plusieurs pays  ont jugé opportun d’adopter les normes IFRS pour des informations de qualité et comparable à travers le monde. C’est dans cet  élan que  l’espace OHADA  décide en 2017 d’harmoniser ses normes à celles d’IFRS. L’objectif de cet article est d’analyser la perception des acteurs sur l’harmonisation des normes OHADA et IFRS. Cette étude qualitative s’appuie sur une population de 16 individus composés d’académiciens et de praticiens de la comptabilité. Les résultats de l’étude révèlent que l’harmonisation du SYSCOHADA aux IFRS était souhaitable mais que certains points de convergences restent questionnable. De plus on ne saurait parler dans le processus d’harmonisation des normes OHADA et des normes IFRS, d’une adoption pure et simple des normes IFRS, mais plutôt d’une adaptation des normes OHADA aux normes IFRS en tenant compte des caractéristiques des pays de l’espace OHADA.
Keywords: Harmonisation; Normes comptables OHADA; Normes comptables internationales; Parties prenantes

Les entreprises françaises et la commande publique en Afrique - Perichon, Lukas (Université Paris-Saclay, 2019)
Les relations contractuelles entre les États africains francophones et les entreprises françaises dans la commande publique se nouent dans un cadre juridique et institutionnel constitué d'un enchevêtrement complexe de normes nationales, régionales et internationales en rupture progressive avec le modèle historique français. Ces relations se formalisent dans des contrats hybrides, aux caractères mal définis, entre contrats publics et contrats internationaux. Ils s'insèrent dans des montages juridiques et financiers où sont mis en balance la profitabilité, l'intérêt général, et les enjeux environnementaux et sociaux du développement. Contractual relationships between french-speaking african countries and french companies in the public procurement sector are formed under a complex network of national, regional and international rules breaking away from the historical french legal and administrative model. These relationships are maintained through ill-defined hybrid contracts that draw from public and international contractual laws and practices. They are integrated into legal and financial frameworks balancing profitability, public interests, environmental and social matters.
Keywords: Africa; Afrique; Afrique francophone; Commande publique; Contrats administratifs; Droit international; Droit public; International law; Marché public; Public law; Public procurement

The Influence of IAS/IFRS on the New OHADA General Chart of Accounts - Tchokoté, Ivan Djossa (Journal of Modern Accounting and Auditing, 2019)
Accounting standardization in black African French-speaking countries is presented through two streams of research. The first stream presents the general chart of accounts common to all these countries as an accounting model which reconciles the divergences between the Anglo-Saxon and continental approaches to accounting, and thereby satisfies the requirements of users of accounting information. The second stream considers that the convergence towards IAS/IFRS is a vital way of attracting international investors and increasing development. This article stands by the second perspective and analyzes the changes introduced in the PCG-OHADA (2017) compared to the PCG-OHADA (2000). It shows that the new provisions of the PCG-OHADA are mainly inspired by IAS 1, IAS 16, IAS 19, IAS 36, IAS 38, IAS 40, and IFRS 6.
Keywords: Accounting harmonization; Accounting standards; IFRS; PCG

Ehe und Familienschutz in Zeiten des demografischen Wandels : ein Rechtsvergleich zwischen dem deutschen und ivorischen Einkommensteuerrecht : mit Überlegungen zur Besteuerung von Ehe und Familie in Entwicklungsländern südlich der Sahara angesichts des „juristischen Erbes Frankreichs“ Vorgelegt von - Kra, Patric Kouassi (Université Paris 10 ; Universität Potsdam, 2019)
De cette étude comparée sur la Côte d’Ivoire et l’Allemagne, il est ressort des similitudes au niveau des garanties juridiques et constitutionnelle de la protection du couple et de la famille en droit fiscal à laquelle s’ajoute la situation de changement démographique. De l’évaluation de la retranscription en droit fiscal de la protection du couple et de la famille il est ressorti que la transcription allemande est élargie, mais désuète. En particulier en raison De l’inadéquation de l’imposition commune des époux avec fractionnement en raison du caractère obsolescent et injuste de la mesure. Concernant la Côte d’Ivoire, l’on constate une transcription ivoirienne ciblée sur le couple et la famille, mais lacunaire du fait de l’inadaptation de la protection pro-nataliste au moyen du quotient familial, la difficulté de recensement effectif des contribuables et le défaut de déduction d’impôts du fait de la famille élargie. Pour le perfectionnement et la modernisation de la transcription fiscale il faut pour l’Allemagne une entière déductibilité des frais de garde d’enfants en raison de l’ activité professionnelle et application du quotient familial sur le modèle français tout en conservant le montant des allocations familiales allemande. Pour la Côte d’Ivoire il est nécessaire de suspendre l’application du quotient familial pour instaurer une imposition individuelle des conjoints tout en autorisant la déductibilité des charges exceptionnelles occasionnées par la famille. From this comparative study on Côte d'Ivoire and Germany, similarities in the legal and constitutional guarantees of the protection of the marriage and the family in tax law are apparent, as well as the situation of demographic change. From the evaluation of the transcription of the protection of the couple and the family into tax law, it emerged that the German transcription is broadened, but outdated. In particular because of the inadequacy of the joint taxation of spouses with splitting due to the obsolescence and unfairness of the measure. Concerning Côte d'Ivoire, there is an Ivorian transcription targeted at the couple and the family, but incomplete because of the inadequacy of pro-natalist protection by means of the family quotient, the difficulty of effectively recording taxpayers and the lack of tax deduction due to the extended family. For the improvement and modernisation of the tax transcription, Germany needs a full deductibility of childcare costs due to professional activity and the application of the family quotient on the French model, while maintaining the amount of German family allowances. For Côte d'Ivoire, it is necessary to suspend the application of the family allowance in order to introduce individual taxation of spouses while allowing the deductibility of exceptional expenses caused by the family.
Keywords: Allemagne; Comparative law; Countries south of the Sahara; Côte d'Ivoire; Droit comparé; Droit fiscal; Droit fiscal allemand; Droit fiscal de la famille; Droit fiscal ivoirien; Famille; Famille (droit); Family quotient; Family tax law; German couple's quotient; German tax law; Ivorian tax law; Pays au sud du Sahara; Quotient du couple allemand; Quotient familial

A comparative appraisal of debt relief measures for no income no assets (NINA) debtors in Nigeria - Osunlaja, Tobi Titilayo (University of Pretoria, 2019)
Nigeria currently has a non-functioning insolvency system; it is yet to record a successful insolvency case. This failure principally is attributable to the weak laws and enforcement policies in existence. The problem is exacerbated by burgeoning consumer debt in the formal sector. The causal factors for this increase in debt are negative economic growth indices such as rising inflation, interest rates and unemployment. With these indices predicted to worsen, a new Bankruptcy and Insolvency Act (BIA) was proposed in 2016. The BIA seeks to regulate individual insolvency proceedings in Nigeria. However, the BIA (as currently conceptualized) does not make provision for debtors with neither income nor assets, often referred to as No Income No Assets (NINA) debtors who, it can be argued, are in the majority in the Nigerian state. The aim in this thesis is to propose debt relief measures that cater for NINA debtors in Nigeria. This proposal aims to prevent further discrimination against these debtors in terms of the current law and the proposed BIA. It envisages that catering for NINA debtors in Nigeria will boost the Nigerian government’s drive to encourage entrepreneurship. In providing for NINA debtors it will provide a safe landing for poor debtors in the event of entrepreneurial failure. The thesis achieves its stated aim by studying international principles and guidelines as espoused by leading bodies. Furthermore, the thesis performs a comparative analysis of relevant NINA provisions in South Africa, Sweden, France, Ireland and Canada. The thesis proposes amendments to the proposed BIA in light of the aforementioned analysis and posits that procedures that are formal and extra-judicial, which have no financial requirements and are easily accessible to debtors should be incorporated.
Keywords: Debt relief measures; Insolvency; Insolvency system; Laws and enforcement policies; No Income No Assets (NINA)

How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit

What Process is Due – Sanctions Regimes of Multilateral Development Banks - Madir, Jelena (University of Westminster, 2019)
Much has been written about the consequences for companies of criminal convictions for bribery and other corrupt practices. However, less attention has been paid to the sanctions regimes that have been developed by multilateral development banks in order to combat fraud and corruption in their operations. This is likely to change in view of the fact that on 9 April 2010, the heads of five leading multilateral development banks (MDBs) – the African Development Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the Inter-American Development Bank and the World Bank Group – signed the Agreement for Mutual Enforcement of Debarment Decisions, which provides for mutual and reciprocal enforcement of debarment decisions taken by any one of them against parties that engage in fraud, corruption, coercion or collusion in connection with MDB-financed projects. For parties that are seeking financing form an MDB or are competing for contracts funded by an MDB, this means that a sanctionable practice committed in a single country could result in global sanctions. Against this background, this thesis examines the type of due process rights that should characterise MDBs’ sanctions procedures. More particularly, the thesis analyses the extent to which MDBs’ sanctions regimes should be bound by the rules of law, analogous to those of national judicial bodies, and the level of due process and transparency that should be required from these ever-evolving regimes. In other words, (how) can the tension between the administrative and business considerations of MDBs’ sanctions regimes (coupled with their immunity from judicial review) be reconciled with due process considerations and principles of fairness that underpin a national judicial model?

Block Chain Accounting: The Face of Accounting and Auditing in Industry 4.0 - Antoney, Laly; Augusthy, Theresa Josephine (International Multilingual Journal of Science and Technology, 2019)
Keywords: Accounting Education; Block Chain Accounting; DLT; Future Audit; Tripple Entry Book Keeping

La responsabilité des ordonnateurs dans le système financier public contemporain : étude comparée des droits camerounais et français - Djeya Kamdom, Yves Gabriel (Université de Lille, 2019)
Comme la France, le Cameroun a hérité du système dit de « budget de moyens» qui met l’accent sur la régularité juridique dans la gestion des finances publiques. Des réformes engagées au cours de la décennie 2000, réorientent leurs systèmes financiers vers la recherche de performance de la dépense publique. En se fondant sur une approche globale des innovations introduites dans le droit public financier des systèmes considérés, ce travail tente de démontrer que la responsabilité des ordonnateurs, certes de nature et d’effectivité variables, ne répond plus uniquement à une logique juridique fondée sur le respect des règles de droit, mais davantage à une logique managériale guidée par la recherche de la performance sur la base d’objectifs établis et de résultats mesurables. Le projet se structure en deux phases. D’une part, la faute sanctionnable, quis’apprécie au regard des obligations qui incombent à l’ordonnateur, est tournée vers la préoccupation de la régularité juridique. D’autre part, cette préoccupation ne prend pas en compte l’exigence de performance, qui est à la base de la loi organique relative aux lois des finances. Just like France, Cameroon inherited what is known as the ''budget by means''system which places emphasis on legal regularity in the management of public finances. However, reforms initiated in the 2000s, gave a fresh orientation to their financial systems by focusing more towards the search for the performance of public expenditure. Based on a global approach to the innovations introduced in the public financial law of the systems under consideration, this work attempts to demonstrate that the responsibility of the authorizing officers, although with some variances as to its nature and effectiveness, no longer only responds to a legallogic based on the respect of the rules of law, but more to a managerial logic guided by the search for performance on the basis of established objectives and measurable results. The project is structured in two phases. On the one hand, the reprehensible fault, which is assessed in the light of the obligations incumbent on the authorizing officer, is directed towards the preoccupation with legal regularity. On the other hand, this concern does not take into account the performance requirement, which is the basis of the organic law bearing on finance laws.
Keywords: Authorizing officers; Cameroun; Comptables publics; Contentieux financier; Finances publiques; Financial litigations; France; Gestionnaires publics; Ordonnateurs; Performance publiques; Public finances; Public performance; Public smanagers; Responsability; Responsabilité; Responsabilité professionnelle

La contribution de l'audit interne dans la gouvernance d'entreprise - El Harchaoui, Es-sahli (Finance & Finance Internationale, 2019)
La gouvernance d’entreprise est une matière vivante, riche, foisonnante qui a connu au cours des dernières années des développements de grande ampleur, tant dans la littérature académique que dans les guides pratiques. L’audit interne constitue un mécanisme de grande importance dans le processus de gouvernance de l’entreprise. De ce fait, considérant le poids et l’importance du rôle de cette fonction sur l’efficacité du système de gouvernance de l’entreprise, nous nous sommes intéressés, dans le cadre de notre étude, aux enjeux et à l’importance de l’audit interne en tant qu’instrument au service de la gouvernance d’entreprise et à l’analyse de sa contribution dans la performance du présent processus. The Corporate governance is a living, rich and abundant subject, which has experienced in recent years major developments, both in academic literature and practical guides. Internal audit is an important mechanism in the process of corporate governance. Therefore, considering the weight and the importance of this function on the efficiency of corporate governance, we will consider, in our study, the issues and the importance of internal audit as a tool serving the corporate governance and analyze its contribution in the performance of this process.
Keywords: Audit committee; Audit interne; Comité d’audit; Contrôle interne; Corporate governance; Gouvernance d'entreprise; Internal audit; Internal control

Le refinancement d'entreprises en difficulté : contribution à l'optimisation juridique du concept de capital-retournement - Feydel, Romain (Université de Limoges, 2019)
Le refinancement d’entreprises en difficulté est entouré d’une grande part de mystification. Aux yeux du grand public, il s’agit avant tout d’un moyen efficace de faire fortune pour les investisseurs s’y aventurant. Cette activité, connue également sous le nom de capital-retournement, est pourtant le domaine d’exercice exclusif de hauts techniciens de la finance et du droit. Le vaste droit de l’ingénierie financière encadre le refinancement d’entreprises en difficulté. Plongeant son lecteur au coeur de la haute finance d’entreprise, cette thèse démystifie le capital-retournement tout en voulant améliorer sa pratique. Pour cela, l’aspect juridique de la levée des fonds et de leur investissement fait l’objet d’une profonde analyse. À partir de celle-ci et de l’inspiration du droit étranger, de nouveaux outils dédiés à l’optimisation du refinancement d’entreprises en difficulté sont proposés. Cette thèse démontre le rôle prépondérant du droit de l’ingénierie financière dans le sauvetage d’emplois en France.
Keywords: Banking and financial law; Droit bancaire; Droit de l'investissement; Droit financier; Droit privé; Fiscalité; Ingénierie financière; Investment Law; Taxation

Electronic Tax System As A Panacea For Tax Revenue Leakages In Nigeria - Nwamgbebu, Obinna; Oketa, Chiamake; Odom, Amarachi; Nwambe, Cynthia; Nweke–Charles, Uchenna (African Journal of Politics and Administrative Studies, 2019)
The broad objective of the study is to assess the problems of the traditional tax system in Nigeria and establish electronic taxation as a solution to these problems. The study adopted content analysis in analyzing text books, journals, newspapers and other essential materials that were used to obtain the needed information for the study. Extensive review of the literature showed that electronic tax system solves the problem of low tax collection, unavailability of tax statistics and poor record keeping, complex of payment and high cost of tax compliance. The implication of these findings is that an adoption of electronic tax system is an intelligent means of achieving a system of tax administration that allows for the collection and accountability of required taxes at a minimum cost. The study concluded that there are some challenges with the manual system of administering taxes and that modern technology could simplify these challenges and alienate them in the form e-tax. The study therefore recommended that government should support with everything on their disposal the establishment of e-tax administration so as to start ripping the benefit of high rate of compliance among taxpayers at all levels of government in Nigeria.

Les règles prudentielles et les immobilisations incorporelles dans l’UEMOA - Alemdjrodo, Richard (Les Annales de droit, 2019)
Les fonds propres (entre autres, les bénéfices non distribués et les autres réserves tels qu’ils figurent au bilan) doivent servir à renforcer les banques. Ainsi, parmi les mesures introduites par Bâle III se trouvent les normes sur le risque de liquidité qui obligent les banques à sélectionner des actifs facilement cessibles sans perte de valeur pour alimenter leur trésorerie en cas de difficulté à cause de retraits massifs de la clientèle ou de l’assèchement du marché interbancaire. En outre, ces mêmes banques ont l’obligation de pondérer leurs actifs selon la qualité du risque. L’une des conséquences de cette obligation de pondération est qu’une augmentation du risque de contrepartie ou le développement des activités de marché devront être compensés par plus de fonds propres. Il est connu que beaucoup d’institutions bancaires à travers le monde ont du mal à respecter les règles prudentielles de Bâle (même les États-Unis ont tardé à adopter Bâle III), cet article a pour but d’analyser le respect du cadre réglementaire de Bâle III par l’Union Économique et Monétaire Ouest-Africain (UEMOA) et sa banque centrale, la Banque Centrale des États de l’Afrique de l’Ouest (BCEAO). Pour y parvenir, il est analysé un exemple de composant des fonds propres, les immobilisations incorporelles, et la politique de la BCEAO (vis-à-vis des institutions de crédit de la zone UEMOA) par rapport à leur prise en compte dans les risques pondérés. Une analyse qui porte à la fois sur le droit bancaire et le droit comptable.
Keywords: banque; fonds propres; immobilisation; incorporel; prudentiel

Adoption, compliance, and consequences of International Financial Reporting Standards in Africa - Tawiah, Vincent K. (Griffith University, 2019)
This thesis investigates the adoption, compliance and consequences of International Financial Reporting Standards (IFRS) in Africa, a continent which has mostly been ignored in prior studies due to the use of generic proxies. Drawing on DiMaggio and Powell (1983), this thesis examines the institutional pressures of IFRS adoption in Africa. Stakeholder salience theory, developed by Mitchell, Agle and Wood (1997), is employed to analyse the determinants of IFRS compliance outside the traditional capital market settings. As regards to the consequences of IFRS in Africa, this thesis analyses the impact of IFRS on audit fees, audit reporting lags and auditor switch. The study used panel data from 54 countries and 205 firms covering the financial years 2003-2016. Secondary data was sourced from reputable database and annual reports of sample companies. Different analytical tools such as ordinary least squares, logit and multinomial regressions were used based on their suitability to address the research questions. The study found that only 18 out of the 54 countries required all listed and large companies to report per IFRS, while 25 did not permit IFRS. The results supported the theoretical prediction that coercive, mimetic, and normative isomorphism influenced IFRS adoption in Africa. Specifically, the World Bank (WB) and International Monetary Fund’s (IMF) influence on African countries in adopting IFRS was not through foreign aid and grants; instead, their recommendations made in the Report on Observance of Standard and Codes (Accounting and Auditing) initiatives. The finding(s) also demonstrated that the presence of global audit firms and the number of years of IFAC membership had a strong association with a country’s decision to adopt IFRS. Moreover, countries with strong professional accounting organisations (PAO) were more likely to adopt IFRS. On IFRS compliance, the study found that the average compliance score among the companies over the period was 70.94%, with a minimum score of 58.59% and a maximum of 83.55%. The findings reported a significant positive association between audit committee competence (ACC) and compliance, and between chartered accountants on board (AOB) and compliance. The thesis also documented that compliance has been increasing over the years. Regarding the impact of IFRS on the audit market, the findings suggested IFRS was positively and significantly associated with an increase in audit fees regardless of early or late adoption. Also, on average, ARL increased by 26% across all samples, with late adopters experiencing 28% and earlier adopters 22% during the adoption year. Contrary to the late adopters, early adopters experienced a significant increase in audit fees during the pre-IFRS period due to the set-up and implementation at the time. In addition, IFRS adoption was likely to cause companies to switch from small audit firms to the Big 4. The findings on adoption suggest that global accounting agencies such as IFAC and IASB should focus on building vibrant national level accounting institutions such as PAOs to facilitate the adoption of IFRS in Africa. The thesis, therefore, adds to the adoption literature the finding that the isomorphic pressures in Africa are different from those suggested in prior studies. The results on compliance imply that companies that appoint more professional accountants to their boards are more likely to comply with the requirement of IFRS. Therefore, it is suggested that companies should engage more chartered accountants in their governance. Also, corporate boards must strive to strengthen their audit committees by appointing more NEDs and CAs to the committee. The findings also provide valuable information for professional accounting organisations on the role of its members (professional accountants) in the effectiveness of IFRS compliance. The findings of the consequences of IFRS on the audit market alert small and medium practitioners (SMPs) in non-IFRS countries of the possible loss of clients to the Big4 due to the adoption of IFRS. To mitigate this effect, the national PAO should build the capacity of their local accountants through training and education to handle the complexities and continuous upgrading of IFRS. Such training is seen as being crucial for SMPs in OHADA countries, Ethiopia, Djibouti and other countries which are in the process of implementing IFRS.
Keywords: Adoption; Africa; Audit market; Compliance; Consequences; IFRS; Institutional pressures; International Financial Reporting Standards; Stakeholder salience

The definitions of ‘inside information’ and ‘insider’ in the Financial Markets Act 19 of 2012 - Van Der Walt, Johann Nico (Stellenbosch University, 2019)
The definitions of ‘insider’ and ‘inside information’ in the Financial Markets Act 19 of 2012 are, as is the case with their international counterparts, central to the Act’s regulation of insider trading. It has long been recognised, however, that those definitions, inherited from repealed companies and market abuse legislation, are cumbersome and counter-intuitive. This state of affairs obtains as the South African legislature has failed to undertake the most fundamental enquiry in formulating a coherent regulatory scheme aimed at prohibiting supposedly wrongful conduct: identifying a single theory of wrongfulness upon which to base its prohibitions. Instead, the definitions include elements of all possible regulatory bases for insider trading, including those having as their object the protection of proprietary rights in information and born out of the fiduciary doctrine. It is argued that the definitions, part of legislation aimed at addressing a financial market wrong, should be formulated with reference to the rights and obligations at play in those markets and the legislature’s objectives for those markets. A proposal is made in that regard.
Keywords: Finance; Financial Markets Act, 2012; Insider trading in securities; Markets; South Africa

Le régime fiscal des implantations internationales d'entreprises : le cas de l'Algérie - Chaouche, Nassima Yelles (Université de Cergy Pontoise; Université d'Oran, 2019)
Depuis longtemps, le critère de rattachement retenu en droit interne et en droit conventionnel pour imposer les entreprises étrangères se fondait sur un principe simple d’application, celui de la territorialité et son corollaire l’établissement stable. Mais avec le phénomène de la globalisation et la numérisation de l’économie, ces règles classiques se révèlent de plus en plus désuètes.Aujourd’hui, les entreprises recourent soit à l’économie numérique, une économie, qui jusque-là reste affranchie de toute taxation ; soit aux transferts indirects de bénéfices pour réduire artificiellement leur bénéfice imposable ou pour transférer des bénéfices vers des pays à faible fiscalité. Cette situation ne fait que stimuler le marché de l’évasion fiscale, d’autant plus que les solutions proposées afin de remédier à ces insuffisances restent pour l’instant embryonnaires vu la résistance de certains Etats et surtout des entreprises. For a long time, the standard of attachment used in domestic law and treaty law to tax foreign enterprises was based on a simple principle of application, that of « territoriality » and its corollary « the permanent establishment ». But with the phenomenon of globalization and the digitization of the economy, these classic rules are proving increasingly obsolete.Today, companies use either the digital economy, an economy that until now has been freed from taxation ; or indirect transfers of profits to artificially reduce their taxable profit or to transfer profits to low-tax countries. This situation stimulates tax evasion, especially since the solutions proposed to remedy these shortcomings remain for the moment embryonic given the resistance of some states and especially companies.
Keywords: Commerce électronique; Prix de transfert

La fiscalité face à l'impératif du développement de la République centrafricaine - Mbounou-Ngopo, Mathurin (Aix-Marseille Université, 2019)
La préoccupation majeure de tout État moderne est d’assurer son développement économique et social. Chaque État définit ses stratégies de développement en fonction de ses réalités. C’est le cas de la République centrafricaine (RCA). L’économie du pays est fragile et demeure marquée par une faible capacité à générer des revenus. En dépit d’un potentiel naturel très important, la RCA pâtit de son enclavement qui pèse sur le développement économique du pays. Or, l’un des problèmes-clés du développement économique est celui de son financement endogène. Si les capacités contributives font défaut, il est impossible d’assurer un développement harmonieux. En effet, le financement du développement d’un État reste tributaire de la performance des ressources fiscales et douanières. La politique fiscale a un rôle important à jouer dans le développement économique d’un pays. En Centrafrique, comme dans les pays en développement, la politique fiscale est la locomotive du développement. Car, l’outil essentiel de toute politique de mobilisation de ressources et de financement adéquat du développement est la fiscalité, véritable instrument de politique économique et sociale. La fiscalité est à ce titre la carte maîtresse des programmes économiques de ce pays qui, non seulement, est enclavé mais doit relever le défi de la reconstruction à la suite des troubles politiques qui l’ont secoué durant des décades. Ainsi, la question du financement endogène du développement en Centrafrique se situe dans un contexte nouveau et doit prendre en compte plusieurs paramètres, en vue d’améliorer la mobilisation des ressources financières nationales permettant d’assurer le financement du développement. The major concern of every modern State is to ensure its economic and social development. Since living conditions are not the same, each State sets its development strategies according to its realities. This is the case of the Central African Republic (CAR). The economy remains fragile and is marked by a low capacity to generate income. Despite its huge natural potential (dense water network, large forest, vast mineral resources, extensive arable land etc.), CAR suffers from its hemmed-in position which weighs on the country's economic development. Yet, one of the key problems of economic development is endogenous funding. If the contributory capacities of citizens are limited, it is impossible to ensure a harmonious development. Indeed, the funding of any State development remains dependent on the performance of tax and customs resources. Thus, fiscal policy has an important role to play in the economic development of a country. In Central Africa, as in developing countries, fiscal policy is the locomotive of development. Since the essential tool of all resource mobilisation and adequate development funding policy is taxation, which is the real instrument of economic and social policy. Taxation is as such the trump card of economic programs of this country which, not only is landlocked but must face the challenge of rebuilding following the political unrest that shook it for more than two decades. In this sense, the question of endogenous financing of Central Africa’s development lies within a new context and must take into account several factors in order to improve the mobilization of domestic financial resources to ensure development growth.
Keywords: Central African Republic; Development; Développement; Développement économique; Financement endogenous; Financement endogène; Fiscalité; Mobilisation des ressources fiscales; Mobilization of tax resources; Politique fiscale; Recettes fiscales; République Centrafricaine; Taxation

Les opérations de regroupement de l'endettement du consommateur - Sawadogo, Rélouindé Béatrice (Université Clermont Auvergne‎, 2019)
Le crédit de regroupement destiné aux ménages et aux particuliers fait aujourd’hui partie intégrante des crédits régis par le code de la consommation. Dans un contexte de multi-endettement le plus souvent inadapté à la situation financière des débiteurs, le recours au regroupement de crédits s’inscrit dans la recherche de solutions par le débiteur pour résorber son malendettement ou mieux gérer son budget. Favorisée entre autres par la baisse des taux d’intérêt, l’offre de crédit de regroupement tend à devenir un outil de conquête de parts de marché. Demeuré longtemps sans encadrement précis, le regroupement de crédits bénéficie désormais d’un cadre strict et contraignant initié par la loi n°2010-737 du 1er juillet 2010 portant réforme du crédit à la consommation. Un encadrement dont la substance porte sur la définition des régimes des opérations de regroupement et leurs conditions de formation très formalistes et de nature consumériste. Cela traduit des avancées innovantes en la matière mais cette règlementation tient insuffisamment compte des spécificités du regroupement d’où la nécessité d’évoluer vers un cadre juridique spécifique plus approprié. Il est en effet nécessaire d’intégrer dans l’encadrement du regroupement la définition de l’opération, son procédé de mise en œuvre et d’autres aspects tenant au processus de restructuration. Ce qui permettra de définir des droits et des devoirs pour les parties prenantes aux crédits regroupés et de mieux tenir compte de la fragilité du consommateur-emprunteur par des mesures de prévention d’un nouvel engrenage dans l’endettement excessif. Le mécanisme du regroupement étant néanmoins susceptible de résorber efficacement le malendettement, il pourrait être utilisé comme mesure de traitement du malendettement dans le cadre des procédures de désendettement. Cela nécessite la définition de conditions d’ouverture du droit du surendettement aux situations de malendettement et de trouver des sources de financement du réaménagement de l’endettement via le crédit de regroupement que proposerait la Commission de surendettement. A propos, se tourner vers l’un des créanciers prêteurs est préconisé, mais il faudrait envisager la mise en place d’un fonds public spécifique de soutien aux particuliers qui financerait subsidiairement ledit crédit en cas d’exercice par le banquier de sa liberté de refuser le crédit. In fine, même si les différentes mesures de traitement du malendettement et du surendettement sont utiles, il est nécessaire et primordial de trouver de meilleurs outils pour les prévenir. The Consolidation of Debts to households and individual customers is now part of the Credit Offer regulated by the French Consumption Code Law.In the framework of multiple debts unfit to the financial situation of the Debtors, the use of debts consolidation is geared towards the search of solutions by Debtors to solve bad debts or better manage their budget. Favored by the decrease of interest rates, the consolidation of debts has evolved as a tool to gain additional market shares. Long Time without any structured monitoring, the consolidation of debts is now structured in a strict and binding framework initiated by the law n°2010-737 of July 2010 amending the consumption debt Law. A framework which is grounded on defining the different types of debts consolidation and the conditions of their creation – This process being very formal and of consumerist type. This entails innovative progress in this area field, but these rules do not take into account the peculiarities of debts consolidation, thus, implying the necessity to evolve towards a more specific legal framework. It is now compulsory to integrate within the framing of Debts Consolidation, the definition of the nature of these operations, their methods of implementation and additional aspects related to the restructuring process. This will allow to define the rights and obligations of the stakeholders to debts Consolidation and take into account the fragility of the consumer-borrower through prevention measures against the threat of falling back into the traps of excessive debts. The mechanisms of debts consolidation is however a potential way to solve excessive debts, it could be used as a healing measure to treat excessive Debts in the framework of deleveraging processes. For that purpose, leveraging one of the creditors can be advocated, but one should also contemplate the setup of a Public Fund to support individual customers, and that would finance alternatively such a credit, if not accepted by the bank.In fine, even though the different treatment measures against excessive and bad debts are useful, it is highly important to find out better tools to prevent those situations.
Keywords: Bad debt; Borrower; Consommateur (protection); Consumer; Consumer protection; Contractual freedom; Credit; Crédit; Crédit de substitution; Debts consolidation; Débiteur et créancier; Emprunteur; Fonds spécifique; France; Information spécifique; Legal framework; Lender; Liable credit; Liberté contractuelle; Malendettement; Multi-debt; Multi-endettement; Prêt responsable; Prêteur; Prêts personnels; Re-negotiation; Reframing, process; Regroupement de crédits; Renégociation; Restructuration, procédé; Risk of excessive debt; Risque de surendettement; Régime juridique; Specific fund; Specific information; Substitution credit; Surendettement

La crise des subprimes : vers un meilleur encadrement des risques financiers et juridiques liés à la titrisation des créances - Akiobé Songolo, Michèle Patricia (Université Laval, 2019)
La titrisation des créances est une opération qui permet aux banques de se financer sur les marchés financiers à moindre coût et sans trop de risques. Pour réaliser l’opération, les banques cèdent les prêts qu’elles ont octroyés à une structure qui se chargera ensuite de les placer auprès des investisseurs. De plus, la titrisation permet également aux banques de gérer les risques liés aux prêts. Avec l’avènement de cette opération, les banques se soucient moins de la qualité et de la capacité financière des emprunteurs. Une fois le prêt accordé, les banques vont créer des portefeuilles de créances qui seront cédés par la suite. Une autre forme de titrisation permet de transférer uniquement le risque lié aux prêts sans toutefois sortir ces prêts du bilan de la banque: c’est la titrisation synthétique. Ces deux formes de titrisation, classique et synthétique, ont été utilisées auxÉtats-Unis et ont contribué à l’explosion de la bulle immobilière qui a entraîné une crise financière en 2008 : la crise des subprimes. La titrisation a donc occasionné le mouvement de contagion des risques qui s’en est suivi sur les marchés financiers. Les subprimes sont des prêts hypothécaires à risque accordés à un taux variable aux ménages américains à faible capacité financière. Le taux est bas les premières années, mais augmente progressivement. Titriser ce type de prêts revient à propager le risque de non-remboursement des emprunteurs à tous les différents intervenants de la chaîne. Et c’est ce qui s’est produit: les taux ont été relevés et les emprunteurs n’ont pas été capables d’assurer le paiement des différentes mensualités entraînant un blocage de tout le circuit. Les choses se sont passées de cette façon parce que, sur les marchés à cette période, l’appât du gain l’avait emporté sur le respect des règles d’encadrement des marchés, quasi inexistantes. Cette thèse propose des solutions d’encadrement du marché financieret de l’opération de titrisation en particulier. Entre la loi du marché, le droit et l’éthique, les recommandations faites dans cette dissertation se veulent complémentaires aux actions des différents régulateurs, nationaux et internationaux.
Keywords: 2008 Financial Crisis; Crise financière 2008; Finances; Marché financier; Morale des affaires; Régulation (Théorie économique); Titrisation

Finansal tabloların tutulması ve hukuksal sonuçları - Aksu Özkan, Raziye (Akdeniz Üniversitesi, 2019)
"Bu çalışmada finansal tabloların işlevleri, çeşitleri, düzenlenmesi ve tutulmasından kaynaklanan hukuksal sonuçlar incelenmiştir. Finansal tablolar, işletmenin finansal durumunun ve finansal performansının biçimlendirilmiş sunumudur. Bu tablolar aracılığıyla, şirketin finansal durumu hakkında bilgilendirme yapılmaktadır. Finansal tablolar, özellikle yabancı yatırımcının şirketlere güvenip yatırım kararı alması açısından önem arz etmektedir. Bu bağlamda, Türk Ticaret Kanunu'nun (TTK) genel gerekçesi beşinci paragrafında, uluslararası piyasaların bir parçası olmak hedefi ortaya konulmuştur. Hedefe ulaşmak için, finansal tabloların uluslararası standartlara göre düzenlenmesi gerekliliğine yer verilmiştir. Hedefe ulaşmada yeterli düzenleme yapılması konusunda Kamu Gözetimi, Muhasebe ve Denetim Standartları Kurumu görevlendirilmiştir. Kurum tarafından yapılan düzenlemeler, uluslararası muhasebe standartlarının çevirisinden ibaret olup, yeterli değildir. TTK ile muhasebe uygulaması arasında köprü kurulamamıştır. Ticaret ve vergi hukuku alanında yer alan düzenlemeler kapsamında iki ayrı uygulama yürütülmektedir. Finansal tabloların işletmenin finansal durumunu, finansal performansını ve nakit akışlarını gerçeğe uygun olarak sunması gereklidir. Kural olarak standartlara uygunluk, bilgilerin gerçeğe uygun şekilde açıklanması için yeterlidir; ancak bu uygunluk gerçek durumunu yansıtmıyorsa standartlar uygulanmayabilecektir. Finansal tablolar bilanço, döneme ait kar veya zarar ve diğer kapsamlı gelir tablosu, özkaynak değişim tablosu, nakit akış tablosu, önemli muhasebe politikalarını ve diğer açıklayıcı bilgileri içeren dipnotlardan oluşur. Bilanço, işletmenin hazırlandığı tarih itibariyle varlık, yükümlülük ve özkaynaklarını gösteren finansal tablodur. İşletmenin sahip olduğu her türlü malvarlığı unsuru veya katlandığı her sorumluluk bilançoda muhasebeleştirilemez. Bunun için standartlarda sayılan koşulları taşımaları gerekmektedir. Bilanço dışındaki diğer finansal tablolar, ya bilançonun hazırlanması açısından birer araçtır ya da bilançonun tamamlayıcısıdır. Tabloların içeriğinde yer alan bilgilerin birbiriyle ilişkisi, bunların bir bütün olarak değerlendirilmesi gerektiğini ortaya koymaktadır. Finansal tabloların tutulmasının yönetim kurulu, denetim ve genel kurul açısından hukuki sonuçları bulunmaktadır. Yönetim kurulu finansal tabloları hazırlar ve genel kurula sunar. Bununla birlikte, denetim finansal tablolar esas alınarak yapılacaktır. Buna bağlı olarak, denetçi şirket hakkında denetim raporunu oluşturacaktır. Genel kurul, denetimden geçmiş finansal tablolara dayanarak şirkete ve yönetim kuruluna ilişkin kararlar alacaktır. In this study, the legal results arising from the functions, types, regulation and retention of the financial statements are examined. Financial statements are a structured representation of the financial position and financial performance of an entity. These tables provide information on the financial position of the company. Financial statements are especially significant for foreign investors to trust companies and make investment decisions. In this context, the fifth paragraph of the general justification of the Turkish Commercial Code (TCC) aims to be a part of international markets. In order to reach the target, it is necessary to arrange the financial statements according to international standards. The Public Oversight, Accounting and Auditing Standards Authority has been appointed to ensure adequate regulation to reach the target. The regulations made by the institution consist of translation of international accounting standards and are not sufficient. No bridge could be established between the TCC and the accounting practice. Within the scope of the regulations in the field of trade and tax law, two different applications are carried out. Financial statements shall present fairly the financial position, financial performance and cash flows of an entity. As a rule, compliance with standards is sufficient for the information to be truthfully disclosed; however, if this compliance does not reflect the actual situation of the company, the standards may not apply. The financial statements comprises balance sheet, a statement of profit or loss and other comprehensive income for the period, a statement of changes in equity, a statement of cash flow, notes, comprising significant accounting policies and other explanatory information. The balance sheet is the financial statement showing the assets, liabilities and equity of the entity. Any asset that the entity owns or any liability that it endures cannot be recognized in the balance sheet. For this, they must meet the requirements listed in the standards. Other financial statements, other than the balance sheet, are either tools for the preparation of the balance sheet or complementary to the balance sheet. For this reason, the relationship between the information contained in the content of the tables suggests that they should be evaluated as a whole. The holding of the financial statements has legal consequences for the board of directors, auditing and general assembly. The Board of Directors shall prepare the financial statements and present them to the General Assembly. However, the audit will be performed on the basis of financial statements. Accordingly, the auditor will establish an audit report on the company. The General Assembly shall take decisions regarding the company and the board of directors on the basis of audited financial statements."
Keywords: Commercial law; Compliance with laws; Financial statements; Finansal tablolar; Hukuka uygunluk; Hukuksal esaslar; International Accounting Standards; Legal aspects; Standards; Standartlar; Ticaret hukuku; Turkish Accounting Standarts; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Türkiye Muhasebe Standartları; Uluslararası Muhasebe Standartları

The tax trade interface : an investigation of the influence of the Nigerian income tax incentives on taxpayer behaviour - Aniyie, Ifeanyichukwu Azuka (University of Pretoria, 2019)
The Companies Income Tax Act provides the architecture for corporate income taxation (CIT) in Nigeria. It specifies the rate, the tax base and contains the bulk of the incentives to which qualified corporate taxpayers are entitled. This thesis investigates the influence of incentives on the compliance behaviour of micro and small companies (MSCs) in Nigeria. By Nigeria’s standard, these are companies which: (1) employ between 1 to 49 persons and/or own assets (excluding land and building) valued at less than NGN 100million; or (2) are either private limited companies or one-man businesses. In the context of the Nigerian tax system, MSCs are corporate taxpayers with turnover of less than NGN 200 million. This choice of research population is a consequence of the globally acknowledged niche occupied by MSCs vis-à-vis the of the socio-economic objectives of any state. In the course of the study, the formulated research questions were resolved using a multi-stage mixed methods framework which allowed for the fusion of qualitative and quantitative epistemology as well as facilitated the introduction of pragmaticism into the research process. The thesis, inter alia, identified gaps in the administrative regime of CIT incentives in Nigeria and highlighted the fact that they have the potential to introduce uncertainty into the tax system. In addition, it revealed that the regulatory regime for the role and services of tax intermediaries within the tax system, in terms of current standards and reality, is sub-optimal. On the basis of a survey of a small sample of MSCs, it was concluded that the influence of tax intermediaries with regard to the compliance behaviour of MSCs was marginal. Reason for this was traced to the fact that the role and services of the latter vis-à-vis clients who are MSCs are actuated by variables which are within the psycho-social space of the tax intermediairies and the desires/requests of the MSC. This dismisses, in the context of Nigeria, the notion that the tax intermediary is the initator of every tax dodge. Based on the findings, the thesis, inter alia, recommended a re-orientation in the conceptualisation of tax compliance as the prevailing theoretical premise for the extant tax law and policy does not contemplate that non-economic factors and referents outside the realm of taxation are capable of influencing tax compliance behaviour. In addition, recommendations with the capacity to change the law, policy and administrative regime relating to CIT incentives as well as the role and services provided by tax intermediaries were made after an examination of the situation in Kenya and South Africa.
Keywords: Companies Income Tax Act; Corporate income taxation; Income tax; Nigeria; Tax trade; Taxpayer

Amélioration de la méthodologie de construction de la courbe des taux sans risque dans la zone UEMOA - Gbongué, Florent (Assurances et gestion des risques / Insurance and Risk Management, 2019)
Dans la zone de l’Union économique et monétaire ouest-africaine (UEMOA), la construction d’une courbe des taux sans risque est un objectif pour les décideurs publics. En effet, elle permet d’accompagner les mutations réglementaires actuelles, ainsi que le processus de développement du marché financier régional (MFR). En s’appuyant sur les conclusions de Gbongué et Planchet (2015) et Gbongué (2019), nous proposons une nouvelle méthodologie de construction de la courbe des taux sans risque, adaptée aux particularités de cette zone, dans l’optique de réduire les erreurs d’estimation de la valeur théorique des obligations souveraines. Notons qu’elle s’appuie sur les fondamentaux du modèle de Nelson et Siegel, dans le but de faciliter la prévision de cette courbe dans le futur.
Keywords: Nelson and Siegel; Nelson et Siegel; UEMOA; courbe des taux sans risque; erreurs d’estimation; estimation errors; fondamentaux; fundamentals; marché financier régional; mutations réglementaires; prediction; prévision; regional financial market; regulatory changes; risk-free interest rate curve

Modernisation of customs regulations and practices to combat customs offences in France, South Africa and Cameroon - Kouamo, Juliette Armelle (North-West University, 2019)
The modernisation of customs regulations and practices involves a process of transformation aimed at boosting the capacity of customs agencies so that they can respond more efficiently to the ever-changing trade environment. In the context of this study, the transformation referred to is changes and adaptations of the institutional, structural, legal, practical, and managerial aspects of revenue collectors’ work. Several global changes in international trade prompted the World Customs Organization (WCO), an international customs body, to pilot projects for the modernisation of customs in order to adapt the approach of this administration to the various changes occurring in the field. These changes relate to the increasing volume of world trade, technological advances, the transformation of businesses models and the steady rise in criminal activities and security threats. The modernisation of customs with the WCO's guidance and support entails inviting and empowering member states of the WCO to align their customs regulations and practices with international standards. Customs modernisation became a topic of interest and started gaining worldwide attention when international trade experienced unprecedented changes coupled with technological advances. This has opened debates around issues relating to globalisation, such as the lowering and removal of trade barriers. There is also a necessity to ensure that customs authorities have sufficient strategic controlover imported and exported commodities. It has become imperative for all states to improve their competitiveness in customs through the revision of regulations which give rise to burdensome practices and procedures. The removal of cumbersome legislative provisions and practices will ensure an increment of efficiency in customs processes.Customs modernisation differs in developed, developing or under-developed states. Hence, the approach to customs modernisation differs from one jurisdiction to another. While some states embrace customs modernisation, others are unable, unwilling or merely reluctant to do so. There are different reasons for the variation in states’ attitudes towards customs modernisation. These attitudes are reflective of the political and economic realities prevailing in each state. Some states are open to customs modernisation but lack the financial and structural resources necessary to be vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools. vii able to engage in such modernisation. Others are plagued by corrupt syndicates which employ all the means at their disposal to defend their manipulation of customs authorities.This study analyses the modernisation of customs regulations and practices in France, South Africa and Cameroon. These jurisdictions have different economic powers, are located in different geo-economic zones, and differ in their capacity to implement customs modernisation. The study examines how the respective states incorporate modernisation into their daily customs operations, as recommended by the WCO, of which they are all member states. The study further analyses the impact of customs modernisation on the fight against customs offences in the three jurisdictions.Changes in international trade have both positive and negative impacts on customs. The negative impacts include changes in the forms and increases in the frequency of customs offences. Customs offences are breaches or attempted breaches of customs laws. States suffer financial loss, and these illegal activities threaten their security. The benefits that accrue to businesses and the quality of their products are also challenged by these unlawful behaviours. In addition, the health and safety of citizens are imperilled by customs offences such as the illicit import of counterfeit, sub-standard and dangerous goods and substances. Irrespective of their nature, customs offences have negative impacts on society.To limit and mitigate the adverse effects of customs offences on society and revenue collection, there is a need for strategic customs administrations that embrace technology and modernisation in general. France, South Africa and Cameroon have modernised their customs administrations. While these countries have incorporated the WCO conventions and tools in their respective environments, the impact of the incorporation on customs offences, in general, can be inferred from the simple implementation of these instruments and tools.
Keywords: Customs modernisation; Customs offences; Customs regulations

Curbing transfer pricing manipulation in South Africa : lessons from selected jurisdictions - Mboweni, Abel Mabawuzeni (University of Pretoria, 2019)
Transfer pricing manipulation is a worldwide problem which results in a massive loss of revenue which is meant to finance government socio-economic programmes. South Africa is not immune to this problem. South Africa is losing billions of Rands in tax revenue due to this scourge. This research is an attempt to find ways and means which can be employed to combat or control the problem. In order to find the envisaged solutions, this research investigates the causes of the problem by analysing the weaknesses and the strong points of the arm’s length principle which is the basis of transfer pricing practice in South Africa and elsewhere. The research also investigates and analyses the corporate reasons for Multinational Enterprises (MNEs) to engage in transfer pricing with a view to demonstrating that transfer pricing is a neutral tax avoidance concept if it is applied for genuine business considerations. The investigation also entails analysing the legal framework of transfer pricing in South Africa which is embodied in section 31 of the Income Tax Act 58 of 1962. The research analyses the efficacy of section 31 in dealing with the sophisticated transfer pricing manipulation schemes. In addition, an extensive reference to the Organisation for Economic Co-operation and Development (OECD) Transfer Pricing Guidelines is made as South Africa relies heavily on the guidelines. A comparative analysis of selected topics is also conducted with the United States (US) and India with a view to drawing lessons from those jurisdictions. Based on the outcome of the analysis and the lessons drawn from the comparative analysis, findings are presented followed by legislative proposals or recommendations which will help to eradicate the problem. It is hoped that implementation of the recommendations taking into account the socio-economic conditions of South Africa will help to deal with the problem.
Keywords: Loss of revenue; South Africa; Tax Revenue; Transfert pricing

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.